2023
DOI: 10.1101/2023.05.22.540805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small extracellular vesicles but not microvesicles fromOpisthorchis viverrinipromote cell proliferation in human cholangiocytes

Sujittra Chaiyadet,
Javier Sotillo,
Michael Smout
et al.

Abstract: Chronic infection withO. viverrinihas been linked to the development of cholangiocarcinoma (CCA), which is a major public health burden in the Lower Mekong River Basin countries, including Thailand, Lao PDR, Vietnam and Cambodia. Despite its importance, the exact mechanisms by whichO. viverrinipromotes CCA are largely unknown. In this study, we characterized different extracellular vesicle populations released byO. viverrini(OvEVs) using proteomic and transcriptomic analyses and investigated their potential ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…So far, two different EV subpopulations (exosomes and MVs) have been identi ed in adult trematode specimens in Fasciola spp., Schistosoma mansoni (Digenea, Schistosomatidae) and O. viverrini [41,[50][51][52]. Similarly, the current EV protein composition of S. chrysophrii indicated that S. chrysophrii has two distinctive EV subpopulations.…”
Section: Extracellular Vesicles Isolation and Transmission Electron M...mentioning
confidence: 94%
“…So far, two different EV subpopulations (exosomes and MVs) have been identi ed in adult trematode specimens in Fasciola spp., Schistosoma mansoni (Digenea, Schistosomatidae) and O. viverrini [41,[50][51][52]. Similarly, the current EV protein composition of S. chrysophrii indicated that S. chrysophrii has two distinctive EV subpopulations.…”
Section: Extracellular Vesicles Isolation and Transmission Electron M...mentioning
confidence: 94%